3D-printed temperature and shear stress-controlled rocker platform for enhanced biofilm incubation - Daniel P. G. Nilsson; Krister Wiklund; Dmitry Malyshev; Magnus Andersson (Scientific Reports)
Abstract Growing biofilms of thermophilic (heat-loving) and psychrotrophic (cold-tolerant) bacteria pose several challenges due to specific environmental requirements. Thermophilic bacteria typically grow between 45 and 80 $$^{° }$$ C, while psychrotrophic bacteria thrive between 0 and 15 $$^{° }$$ C. Maintaining the precise temperature and fluid conditions required for biofilm growth can be technically challenging. To overcome these challenges, we designed the Bio-Rocker, a temperature- and shear stress-controlled rocker platform for biofilm incubation. The platform supports temperatures between − 9 and 99 $$^{° }$$ C, while its digital controller can adjust the rocking speed from 1 to 99 $$^{° }$$ /s and set rocking angles up to ±19 $$^{° }$$ . This ability, together with data from analytical models and multi-physics simulations, provides control over the shear stress distribution at the growth surfaces, peaking at 2.4 N/m $$^2$$ . Finally, we evaluated the system’s ability to grow bacteria at different temperatures, shear stress, and materials by looking at the coverage and thickness of the biofilm, as well as the total biomass. A step-by-step guide, 3D CAD files, and controller software is provided for easy replication of the Bio-Rocker, using mostly 3D-printed and off-the-shelf components. We conclude that the Bio-Rocker’s performance is comparable to high-end commercial systems like the Enviro-Genie (Scientific Industries) yet costs less than $350 dollars to produce.